2021
DOI: 10.1002/cptc.202100062
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable, Bifunctional Metallaphotocatalysts for C−S Cross‐Coupling Reactions

Abstract: Metallaphotocatalytic cross‐coupling reactions are typically carried out by combining homogeneous or heterogeneous photocatalysts with a soluble nickel complex. Previous attempts to realize recyclable catalytic systems use immobilized iridium complexes to harvest light. We present bifunctional materials based on semiconductors for metallaphotocatalytic C−S cross‐coupling reactions that can be reused without losing their catalytic activity. Key to the success is the permanent immobilization of a nickel complex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…It is noteworthy that this substrate was earlier reported as a successful coupling partner when NiCl2•bpy was used in combination with tris(2,2'bipyridyl)dichlororuthenium(II) hexahydrate as exogenous photocatalyst. 30 With regard to the aryl iodide, the reaction affords the corresponding sulfones in presence of electron withdrawing groups such as trifluoromethyl (1), nitrile (8), ketone (9)(10)(11), amide (12), boron pinacolate ester (13), and methyl ester (14). Para-( 9) and ortho-( 11) substitution showed similar reactivity, whereas meta-substitution (10) required a longer reaction time for full conversion.…”
Section: Scope and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that this substrate was earlier reported as a successful coupling partner when NiCl2•bpy was used in combination with tris(2,2'bipyridyl)dichlororuthenium(II) hexahydrate as exogenous photocatalyst. 30 With regard to the aryl iodide, the reaction affords the corresponding sulfones in presence of electron withdrawing groups such as trifluoromethyl (1), nitrile (8), ketone (9)(10)(11), amide (12), boron pinacolate ester (13), and methyl ester (14). Para-( 9) and ortho-( 11) substitution showed similar reactivity, whereas meta-substitution (10) required a longer reaction time for full conversion.…”
Section: Scope and Limitationsmentioning
confidence: 99%
“…6 Moreover, nickel complexes and visible-light photocatalysts were combined in bifunctional heterogeneous materials, such as metal-organic frameworks, 8,9 organic polymers, 10 or functionalized semiconductors. [11][12][13][14] Although dual photo/nickel catalysis is attractive, the need for a photocatalyst is a drawback. Commonly applied homogeneous noble-metal based photocatalysts that are mainly applied are expensive, not easily recyclable and unsustainable.…”
Section: Main Introductionmentioning
confidence: 99%
“…A comparison of different aryl halides showed that an aryl iodide reacts significantly faster than the corresponding bromide (14). This is in contrast to dual nickel/photocatalytic protocols, where iodides and bromides exhibit similar reactivity.…”
Section: Scope and Limitationsmentioning
confidence: 88%
“…Under optimized conditions, the light-mediated, nickel-catalyzed N-arylation of sulfonamides afforded 3 in 75% yield (entry 13). Light and the nickel salt were crucial for product formation (entry [13][14].…”
Section: Ligand Design and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation